Analisis Kinerja Keuangan Pada Koperasi Pegawai Pemerintah Daerah (KOPEMDA) Kabupaten Maros - Baharuddin Baharuddin (Jurnal Online Manajemen ELPEI, 2021)
This study aims to analyze the financial performance of the Regional Government Employee Cooperative (KOPEMDA) Maros Regency in 2018 – 2020. This research uses several ratio analysis methods, including liquidity ratios, solvency ratios, activity ratios and profitability ratios. The data source used in this research is primary data in the form of financial reports for the period 2018 - 2019 obtained directly from KOPEMDA Maros Regency. Based on the results of the analysis carried out, it can be concluded that cooperative liquidity in terms of the current ratio is declared illiquid. The solvency ratio in terms of the debt to assets ratio and debt to equity ratio of cooperatives is declared solvable. In terms of the activity ratio, in terms of working capital, turnover is stated to be healthy, while receivable turnover is stated to be very unhealthy. The profitability ratio in terms of return on assets is stated to be unhealthy, while the return on equity is stated to be unhealthy.